Estudio y oferta de una red de telecontrol para la unidad educativa Enrique Ponce Luque; cantón Quevedo, año 2015 - Albiño Ortega, Bélgica Amada (2015)
This paper is divided into five chapters that correspond to study and offer a remote control system for the educational unit Enrique Ponce Luque city of Quevedo, here first addresses an introductory phase of the theoretical principles of remote and then make the diagnosis the current state to form the basis for the design of the solution, it also focuses on the work done on this subject in articles found on the Web. The design phases according to ADDIE model comprising five phases was developed: Analysis, design, development, implementation (implementation and implementation) and evaluation, in which evidence of the communication technology specifications, instrumentation and left automation necessary this accompanied by the technical specifications of equipment in each case. Hardware determined necessary based on the type of work to be done, was configured and Script Development for proper programming of the elements that make up the remote. The application to control the electronic system is designed in PHP code is free software. At the end an economic analysis is performed on the proposal to determine the costs of implementation, these costs amount to $ 12,320, which is considered adequate, however costs may rise if desired further expand service coverage.